Critical Review of XBRL Financial Reporting: Perspective Pancasila as One of Indonesia’s National Defense Values - Gideon Setyo Budiwitjaksono; Munari Munari; Diah Hari Suryaningrum (JASF: Journal of Accounting and Strategic Finance, 2024)
Implementing XBRL (eXtensible Business Reporting Language) reporting, which has been mandatory since 2015, has been a significant development in Indonesia. However, as a concept adopted from developed countries, XBRL may not fully align with Indonesia's national defense values of Pancasila. This research critically reviews the implementation of XBRL financial reporting, emphasizing its alignment with Pancasila as one of the Indonesian national defense values. This study focuses on the implementation, challenges, and impact of XBRL financial reporting. To further understand the relationship between Pancasila and XBRL, this study uses case studies on three government banks, the pioneers in implementing XBRL financial reporting. The critical analysis, particularly from the perspective of Pancasila values, demonstrates that XBRL can enhance the integrity, standardization, transparency, comparability, and public trust in companies, thereby positively impacting long-term performance. These findings not only provide a crucial basis for further research but also offer practical implications for companies to immediately implement XBRL, aligning with the Pancasila as the noble values of the Indonesian nation.